Head growth in fetuses with isolated congenital heart defects: lack of influence of aortic arch flow and ascending aorta oxygen saturation. (2nd August 2016) - Jansen, F. A. R.; van Zwet, E. W.; Rijlaarsdam, M. E. B.; Pajkrt, E.; van Velzen, C. L.; Zuurveen, H. R.; Kragt, A.; Bax, C. L.; Clur, S.‐A. B.; van Lith, J. M. M.; Blom, N. A.; Haak, M. C.
Abstract : Linked Comment: Ultrasound Obstet Gynecol 2016; 48: 282–282 ABSTRACT: Objectives: Congenital heart defects (CHDs) are reported to be associated with a smaller fetal head circumference (HC) and neurodevelopmental delay. Recent studies suggest that altered intrauterine brain hemodynamics may explain these findings. Our objectives were to evaluate the pattern of head growth in a large cohort of fetuses with various types of CHD, analyze these patterns according to the type of CHD and estimate the effect of cerebral hemodynamics with advancing gestation in the second and third trimesters. Methods: Singleton fetuses with an isolated CHD were selected from three fetal medicine units ( n = 436). Cases with placental insufficiency or genetic syndromes were excluded. CHD types were clustered according to the flow and oxygen saturation in the aorta. Z ‐scores of biometric data were constructed using growth charts of a normal population. HC at different gestational ages was evaluated and univariate and multivariate mixed regression analyses were performed to examine the patterns of prenatal HC growth. Results: Fetuses with severe and less severe types of CHD demonstrated statistically significant HC growth restriction with increasing gestational age (slope of −0.017/day); however, there was no statistically significant effect of fetal hemodynamics on HC growth. Fetuses with CHD but normal brain oxygenation and normal aortic flow showed a significant decrease in HC growth (slope of −0.024/day). Only fetuses with isolated tetralogy of Fallot demonstrated a smaller HC z ‐score at 20 weeks of gestation (−0.67 (95% CI, −1.16 to −0.18)). Conclusions: Despite the decline in head growth in fetuses with a prenatally detected isolated CHD, HC values were within the normal range, raising the question of its clinical significance. Furthermore, in contrast to other studies, this large cohort did not establish a significant correlation between aortic flow or oxygen saturation and HC growth. Factors other than altered fetal cerebral hemodynamics may contribute to HC growth restriction with increasing gestational age, such as (epi)genetic or placental factors. Copyright © 2016 ISUOG. Published by John Wiley & Sons Ltd.